The Effect of International Trade on Foreign Exchange Reserves in Indonesia 2016-2021 - Zendato, Novita Ria; Sekali, Andri Agrifa Karo; Matondang, Khairani (PT. Riset Press International, 2023)
This study was conducted to analyze BPS data to find out where international trade, such as imports and exports, has an impact on Indonesia's foreign exchange. The study was conducted by collecting data from various statistical databases available at BPS. The Data were reviewed from the period 2016 to 2021. A quantitative study of the impact of international trade on currencies using the difference between exports (x1) and imports (x2) and currencies (y). Multiple analysis using SPSS applications 22. Based on the research results of data analysis, it can be concluded that international trade ie. imports and exports have a significant impact on the Indonesian currency. Exports and imports have different roles in the impact of currency, exports can lead to currency declines.